Phytochemical Enhancement in Broccoli Florets after Harvest by Controlled Doses of Ozone - Arturo Duarte-Sierra; Charles F. Forney; Minty Thomas; Paul Angers; Joseph Arul (Foods, 2022)
The objective of this work was to examine the effect of controlled doses of O3 (0, 5 µL L−1 of O3 for 60 min, and 5 µL L−1 of O3 for 720 min) on the quality and phytochemical content of broccoli florets during postharvest storage. The optimal dose was found at 5 µL L−1 of O3 for 60 min, from the color retention of broccoli florets exposed to the gas treatment. Overall, the antioxidant capacity of the florets was significantly affected by both doses of O3 compared to the non-exposed florets. The profile of glucosinolates was determined for up to 14 days in broccoli florets stored at 4 °C by LC-MS. The amount of total glucobrassicins and total hydroxy-cinnamates in florets significantly (p ≤ 0.05) improved by the application of 5 µL L−1 of O3 for 60 min compared to non-treated florets. The up-regulation of genes of the tryptophan-derived glucosinolate pathway was observed immediately after both treatments. The gene expression of CYP79A2 and CYP79B3 in broccoli was significantly higher in broccoli florets exposed to 5 µL L−1 of O3 for 720 min compared to non-exposed florets. Although enhancement of secondary metabolites can be achieved by the fumigation of broccoli florets with low doses of ozone, quality parameters, particularly weight loss, can be compromised.